2017
DOI: 10.1002/jcph.887
|View full text |Cite
|
Sign up to set email alerts
|

Results From the First‐in‐Human Study With Ozanimod, a Novel, Selective Sphingosine‐1‐Phosphate Receptor Modulator

Abstract: The sphingosine‐1‐phosphate 1 receptor (S1P1R) is expressed by lymphocytes, dendritic cells, and vascular endothelial cells and plays a role in the regulation of chronic inflammation and lymphocyte egress from peripheral lymphoid organs. Ozanimod is an oral selective modulator of S1P1R and S1P5R receptors in clinical development for the treatment of chronic immune‐mediated, inflammatory diseases. This first‐in‐human study characterized the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of ozanimod in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 23 publications
6
97
0
Order By: Relevance
“…Receptor desensitization, internalization, and degradation of the cardiac S1P 1R have been proposed to explain the time‐related attenuation of heart‐rate effects . In a previous phase 1 single‐ascending‐dose and multiple‐ascending‐dose study with ozanimod, a mild dose‐dependent, first‐dose reduction in HR was observed, which was attenuated with an increasing dose‐escalation regimen . No further reduction in HR was observed when the ozanimod dose was escalated up from 1 mg to 2 mg in this study, confirming the effectiveness of the dose‐escalation regimen employed in this TQT study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Receptor desensitization, internalization, and degradation of the cardiac S1P 1R have been proposed to explain the time‐related attenuation of heart‐rate effects . In a previous phase 1 single‐ascending‐dose and multiple‐ascending‐dose study with ozanimod, a mild dose‐dependent, first‐dose reduction in HR was observed, which was attenuated with an increasing dose‐escalation regimen . No further reduction in HR was observed when the ozanimod dose was escalated up from 1 mg to 2 mg in this study, confirming the effectiveness of the dose‐escalation regimen employed in this TQT study.…”
Section: Discussionsupporting
confidence: 78%
“…Following oral administration, the median time to maximum concentration (T max ) was approximately 8.0 hours. Ozanimod exhibited linear PK, with a dose‐proportional increase in exposure and low to moderate intersubject variability; a high steady‐state volume of distribution; a moderate apparent oral clearance; and an elimination half‐life of 17 to 21 hours . Ozanimod is eliminated primarily via biotransformation followed by biliary excretion .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The safety, pharmacokinetics (PK), and pharmacodynamics of ozanimod hydrochloride (HCl) in single oral doses (up to 3 mg) and multiple oral doses (up to 2 mg once daily) were characterized in a phase 1 study of healthy volunteers . Following oral administration under fasting conditions, the median time to maximum concentration (T max ) was approximately 8 hours .…”
mentioning
confidence: 99%
“…The safety, pharmacokinetics (PK), and pharmacodynamics of ozanimod hydrochloride (HCl) in single oral doses (up to 3 mg) and multiple oral doses (up to 2 mg once daily) were characterized in a phase 1 study of healthy volunteers . Following oral administration under fasting conditions, the median time to maximum concentration (T max ) was approximately 8 hours . Ozanimod exhibited linear PK, with dose‐proportional increases in exposure and low to moderate intersubject variability (% coefficient of variation, 17%–32%), high apparent volume of distribution (81.9 L/kg), moderate apparent oral clearance (233 L/h), and elimination half‐life of approximately 17 hours .…”
mentioning
confidence: 99%